UJI EFEK ANTIPIRETIK INFUSA DAUN SESEWANUA (Clerodendron squamatum Vahl.) TERHADAP KELINCI JANTAN YANG DIINDUKSI VAKSIN DTP HB - Moot, Clementia Luigy; Bodhi, Widdhi; Mongi, Jeane (UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACTSesewanua leaves (Clerodendron squamatum Vahl.) empirically used for an alternavite fevertreatment. The aims of this study was to investigate infuse of Sesewanua leaves hadantipyretic effectts for rabbits induced by vaccine DTP HB. This assay uses 15 rabbitsgrouped into 5 groups, the negative control (destilled water), the treatment (infuse ofSesewanua leaves 20%, 40% and 80%) and a positive (parasetamol). Rabbits induced pyrexiawith vaccine DTP HB doses 0,25ml/KgBB by intramuscular route. Rabbit’s rectaltemperature was measured every 1 hour until 4 hours after the oral administration. Thedecrease of rabbit’s rectal temperatur were analyzed by one way ANOVA and LSD test (α =0,05%). The result showed that infuse of Sesewanua in concentrates 20%, 40% and 80% hadantipyretics effect for rabbits induced by vaccine DTP HB.Keywords : Antipyretics effect test, Clerodendron squamatum Vahl., Vaccine DTP HB,rabbits